HUBUNGAN KADAR HB, PERAWATAN LUKA DAN DM TERHADAP KEJADIAN INFEKSI LUKA OPERASI (ILO) PADA PASIEN POST SC DI RSUD H. BADARUDDIN KASIM TANJUNG - Dewi, Ratih Kartika; Kabuhung, Elvine Ivana; Hidayah, Nurul (Jurnal Anestesi, 2024)
One of the patient safety indicators related to medical treatment of surgical wound infection is the main complication experienced by hospitalized patients, the determinants of the cause of surgical wound infection (ilo) post sectio caesaria are DM sufferers, wound care and HB levels Objective: determine hb levels, wound care and DM related to the incidence of surgical wound infection in post sc patients at H. Badaruddin Kasim Tanjung Hospital. The quantitative research method with the research design design carried out is a retrospective, retrospective observational study. The total population of 40 post-SC mothers in 2022 in September - December, total sampling technique. The data was analyzed using the Chi Square test. The results of the study found that there was a relationship between hb levels and ILO incidence in post sc patient respondents, p values = 0.001 and ? = 0.05, p < ?, there was a relationship between wound care and ILO events in post sc patient respondents, p values = 0.000 and ? = 0.05, p < ? and there was a relationship between dm and ILO events, p values = 0.000 and ? = 0.05, p < ?.